Surgical outcomes following nerve transfers in upper brachial plexus injuries - Bhandari P; Sadhotra L; Bhargava P; Bath A; Mukherjee M; Bhatti Tejinder; Maurya Sanjay (Indian Journal of Plastic Surgery, 2009)
Background: Brachial plexus injuries represent devastating injuries with a poor prognosis. Neurolysis, nerve repair, nerve grafts, nerve transfer, functioning free-muscle transfer and pedicle muscle transfer are the main surgical procedures for treating these injuries. Among these, nerve transfer or neurotization is mainly indicated in root avulsion injury. Materials and Methods: We analysed the results of various neurotization techniques in 20 patients (age group 20-41 years, mean 25.7 years) in terms of denervation time, recovery time and functional results. The inclusion criteria for the study included irreparable injuries to the upper roots of brachial plexus (C5, C6 and C7 roots in various combinations), surgery within 10 months of injury and a minimum follow-up period of 18 months. The average denervation period was 4.2 months. Shoulder functions were restored by transfer of spinal accessory nerve to suprascapular nerve (19 patients), and phrenic nerve to suprascapular nerve (1 patient). In 11 patients, axillary nerve was also neurotized using different donors - radial nerve branch to the long head triceps (7 patients), intercostal nerves (2 patients), and phrenic nerve with nerve graft (2 patients). Elbow flexion was restored by transfer of ulnar nerve motor fascicle to the motor branch of biceps (4 patients), both ulnar and median nerve motor fascicles to the biceps and brachialis motor nerves (10 patients), spinal accessory nerve to musculocutaneous nerve with an intervening sural nerve graft (1 patient), intercostal nerves (3rd, 4th and 5th) to musculocutaneous nerve (4 patients) and phrenic nerve to musculocutaneous nerve with an intervening graft (1 patient). Results: Motor and sensory recovery was assessed according to Medical Research Council (MRC) Scoring system. In shoulder abduction, five patients scored M4 and three patients M3+. Fair results were obtained in remaining 12 patients. The achieved abduction averaged 95 degrees (range, 50 - 170 degrees). Eight patients scored M4 power in elbow flexion and assessed as excellent results. Good results (M3+) were obtained in seven patients. Five patients had fair results (M2+ to M3).